Doctor Civil Responsibility In Medical Negligence Atrelated Medical Surgeryagreementactionmedical (Informed Consent) - Hendri Farozah; Arief Wisnu Wardhana (Universitas Muhammadiyah Sumatera Utara, 2023)
The existence of informed consent is very important for the party making the health service agreement, so that it can be seen that the existence of informed consent is very important and necessary when sick. The formulation of the problems in this study are 1) What is the civil responsibility of doctors in medical negligence in medical operations related to informed consent? 2) What is the position of awareness of medical action (Informed Consent) regarding the civil responsibility of doctors in medical negligence in medical operations? The research method used is normative juridical research. The data sources used in this study consist of secondary data. Based on the results of the study, it shows that 1) Position of Medical Action Agreement (Informed Consent) to the civil obligations of doctors in medical recognition of medical operations, namely as a means of self-defense against the possibility of claims or lawsuits from patients or their families if one day unwanted consequences arise so as to provide a sense of security in carrying out medical treatment of patients..; 2) Civil Liability of Doctors in Medical Negligence in Medical Operations Related to Medical Action Agreement (Informed Consent) by compensating for material losses in the form of compensation for expenses that have been made by patients to pay all hospital costs and other treatment expenses as well . loss for not being able to work. Meanwhile, non-material losses due to feelings of illness, anxiety, depression and so on, by fulfilling the elements of default, the patient can hold the doctor responsible for what he has suffered. Patients can file a lawsuit against the doctor to the District Court where there is a dispute. Because the doctor's actions are contrary to the principles of decency, prudence and prudence are expected of him which is based on law on default regulated in article 1239 of the Civil Code and failure regulated in article 1366 of the Civil Code and unlawful acts regulated in article 1365 of the Civil Code